1984
DOI: 10.2355/isijinternational1966.24.923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electromagnetic Stirring at the Final Stage of Solidification of Continuously Cast Strand

Abstract: It is commonly observed that severe V-channel segregates are associated with the equi-axed crystal zone in the central region of a continuously cast strand. This type of segregation may deteriorate the qualities of products especially for sour gas service. The modification of V-segregates is found to be attained by electromagnetic stirring at the final stage of solidification of casts. The laboratory scale stirring experiments have been carried out in order to eliminate V-segregation and the f ollowing results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The benefits of M‐EMS were widely recognized by metallurgists and industries: enlarging the equiaxed crystal zone, reducing center segregation and porosity, intensifying the fluid flow, heat, and mass transfer near the meniscus, helping the removal of inclusions from the molten steel. Many studies investigated the effect of M‐EMS on the inner quality of continuous casting (CC) blooms including center segregation, center porosity, and equiaxed crystal ratio by industrial trials. In the past decades, the effect of M‐EMS on fluid flow, temperature distribution, species transfer, and removal of inclusions was numerically simulated .…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of M‐EMS were widely recognized by metallurgists and industries: enlarging the equiaxed crystal zone, reducing center segregation and porosity, intensifying the fluid flow, heat, and mass transfer near the meniscus, helping the removal of inclusions from the molten steel. Many studies investigated the effect of M‐EMS on the inner quality of continuous casting (CC) blooms including center segregation, center porosity, and equiaxed crystal ratio by industrial trials. In the past decades, the effect of M‐EMS on fluid flow, temperature distribution, species transfer, and removal of inclusions was numerically simulated .…”
Section: Introductionmentioning
confidence: 99%
“…Voller and Beckermann [8] showed that, that his model agreed better with the experimental data of across a wide range of cooling conditions, this model is able Matsumiya et al [17] than did predictions using Eq. [4]. Howto match full coarsening model results by simply adopting ever, Voller et al [8] pointed out that the performance of a constant value of ␣ C ϭ 0.…”
Section: Previous Workmentioning
confidence: 99%
“…where C L,i is the liquid concentration of a given solute eleTo satisfy this requirement, Ohnaka [33] presented a simple ment at the solid-liquid interface, C 0,i is the initial liquid modification of ␤ i to replace Eq. [4]. It is based on compariconcentration, k i is the equilibrium partition coefficient for son with approximate solutions of the diffusion equation for that element, and f S is the solid fraction.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In the final solidification zone, final electromagnetic stirring (F-EMS) was utilized to optimize the porosity and macrosegregation in the center of the billet or bloom. [10][11][12] For the 260 mm  300 mm bloom continuous caster of bearing steel, Yang et al [13] found that the center segregation of carbon decreased with the increasing current intensity of M-EMS. When 300 A of current intensity was applied, the center carbon segregation index of the bloom was 1.04 and the carbon segregation index in the cross section of the bloom was within the range of 0.95-1.05.…”
Section: Introductionmentioning
confidence: 99%